Parental competence programs to promote positive parenting and healthy lifestyles in children: a systematic review - Cayetana Ruiz‐Zaldibar; Inmaculada Serrano‐Monzó; Agurtzane Mujika (Brazilian Society of Pediatrics, 2018)
Objective: To analyze the available evidence regarding the efficacy of interventions on parents whose children were aged 2-5 years to promote parental competence and skills for children's healthy lifestyles. Source: Articles published in English and Spanish, available at PubMed, Psycinfo, CINAHL, Web of Science, Eric, and Cochrane Library were reviewed. Summary of the findings: The literature search yielded 2282 articles. Forty‐one full texts were retrieved and assessed for inclusion using the PRISMA flow diagram. Twenty‐six articles were excluded, as they did not meet the inclusion criteria. In the end, 15 studies were included. The studies were conducted between 2003 and 2016, nine in North America, four in Europe, and two in Asia. Extracted data were synthesized in a tabular format. CASPe guide was used to assess the quality of studies that was moderate overall. Parental self‐efficacy was the main construct assessed in most studies. Four studies reported an increase in parental self‐efficacy, although most of them were studies without control groups. Conclusions: Outcomes of interventions to improve parental competence in order to promote children's lifestyles are promising, but inconsistent. Additional studies with higher methodological and conceptual quality are needed. Resumo: Objetivo: Analisar as evidências disponíveis com relação à eficácia de intervenções em pais de filhos entre dois e cinco anos para promover a competência e as habilidades dos pais a respeito de estilos de vida saudáveis para as crianças. Fonte: Foram analisados artigos publicados em PubMed, Psycinfo, CINAHL, Web of Science, Eric e Biblioteca Cochrane. Inglês e espanhol. Resumo dos achados: A pesquisa da literatura encontrou 2.282 artigos; 41 textos completos foram selecionados e avaliados para inclusão com o fluxograma Prisma; 26 artigos foram excluídos, pois não atendiam aos critérios de inclusão. Por fim, 15 estudos foram incluídos. Os estudos foram feitos entre 2003 e 2016. Nove estudos foram conduzidos na América do Norte, quatro eram de origem europeia e dois de origem asiática. Os dados extraídos foram sintetizados em formato de tabela. O guia CASPe foi usado para avaliar a qualidade dos estudos, que, em geral, foi moderada. A autoeficácia dos pais foi o principal dado avaliado na maioria dos estudos. Quatro estudos relataram um aumento na autoeficácia dos pais, apesar de que a maioria era de estudos sem grupo de controle. Conclusões: Os resultados de intervenções para melhorar a competência dos pais para promover os estilos de vida das crianças são promissores, porém incoerentes. São necessários estudos adicionais com melhor qualidade metodológica e conceitual. Keywords: Parenting, Life style, Childhood, Health promotion, Systematic review, Parental support, Palavras‐chave: Parentalidade, Estilo de vida, Infância, Promoção de saúde, Revisão sistemática, Apoio parental